Roguish Self-Fashioning and Questing in Aleksandar Hemon’s “Everything” - Blake, Jason (Text Matters: A Journal of Literature, Theory and Culture, 2019)
This paper examines self-fashioning in Aleksandar Hemon’s “Everything,” a story about a Sarajevo teenager’s journey through ex-Yugoslavia to the Slovenian town of Murska Sobota. His aim? “[T]o buy a freezer chest for my family” (39). While in transit, the first-person narrator imagines himself a rogue of sorts; the fictional journey he takes, meanwhile, is clearly within the quest tradition. The paper argues that “Everything” is an unruly text because by the end of the story the reader must jettison the conventional reading traditions the quest narrative evokes. What begins as a comic tale about a minor journey opens out, in the story’s final lines, into a story about larger historical concerns, namely, the Yugoslav wars of the 1990s. By introducing contemporary history, Hemon points beyond the closed world of his short story, while rejecting the quest pattern he has established.